Differences in run-up, take-off, and flight characteristics: successful vs. unsuccessful high jump attempts at the IAAF world championships - Nicholson, Gareth; Epro, Gaspar; Merlino, Stéphane; Walker, Josh; Bissas, Athanassios (Frontiers in Sports and Active Living, 2024)
Studies previously conducted on high jump have yielded important information regarding successful performance. However, analyses in competitive scenarios have often disregarded athletes’ unsuccessful attempts. This study aimed to investigate the biomechanical differences between successful and unsuccessful jumps during competition. High-speed video footage (200 Hz) was obtained from 11 athletes during the 2018 Men's World Athletics Indoor Championship Final. From each athlete, one successful (SU) and one unsuccessful (UN) jump at the same bar height were included in the analysis, leaving seven athletes in total. Following whole-body 3D manual digitization, several temporal and kinematic variables were calculated for the run-up, take-off, and flight phases of each jump. During SU jumps, athletes raised the center of mass to a greater extent (p < 0.01) from take-off. Touchdown in SU jumps was characterized by a faster anteroposterior velocity (p < 0.05), lower backward lean (p < 0.05), and changes in joint angles for the stance and trail limbs (p < 0.05). Athletes also shortened the final contact time during SU jumps (p < 0.01) after producing a longer flight time in the final step of the run-up (p < 0.05). Elite-level high jumpers undertake a series of adjustments to successfully clear the bar after UN jumps. These adjustments reinforce the importance of the run-up in setting the foundations for take-off and bar clearance. Furthermore, the findings demonstrate the need for coaches to be mindful of the adjustments required in stance and trail limbs when looking to optimize feedback to athletes during training and competition.